Induced-Coagulated Plasma-Fibrin Gels as a Biological Scaffold for Cell Attachment and Proliferation of Umbilical Cord-Derived Mesenchymal Stem Cells (UC-MSC) - Rio Hermantara; Fiano A. Kerans; Rizal R; E. Henny Herningtyas; Lutfan Lazuardi (Universitas Gadjah Mada, 2014)
Fibrin gels are an ideal natural biological scaffold for tissue engineering because they are biocompatible,biodegradable, and have many biological surface markers. However, most research on fi brin gels used commercialfi brin kits that could be costly and limited in some areas. In this study, fi brin gels were made by inducing bloodcoagulation by adding a common diagnostic kit to assess the time for blood to clot, called activated partialthromboplastin time (aPTT). This induced coagulated plasma (iCoplas)-fi brin gels was evaluated for its ability toenhance biological activity of umbilical cord-derived mesenchymal stem cell (UC-MSC), which were cell attachmentand proliferation. Fibrinogen concentration had infl uence on cell attachment, where only 50% of the cells couldattach to 77 mg/dl fi brinogen gels whereas 93% cells adhered to 154 mg/dl fi brin gels. There were no signifi cantdifferences in cell proliferation on polysterene culture dish and fi brin gels (p>0.05). These results showed thatiCoplas-fi brin gels could be used as a fi brin-based scaffold, yielding no signifi cant difference than polysterene-tissueculture dish cultures in cell attachment and cell proliferation on 154 mg/dl fi brinogen concentration.